2009
DOI: 10.1007/s00122-009-1201-4
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the avenue of intersubgenomic heterosis in oilseed Brassica

Abstract: Accumulated evidence has shown that each of the three basic Brassica genomes (A, B and C) has undergone profound changes in different species, and has led to the concept of the "subgenome". Significant intersubgenomic heterosis was observed in hybrids between traditional Brassica napus and first generation lines of new type B. napus. The latter were produced by the partial introgression of subgenomic components from different species into B. napus. To increase the proportion of exotic subgenomic components and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 32 publications
0
55
1
Order By: Relevance
“…Several studies have demonstrated the value of utilizing allelic diversity of the allied Brassica species for increased heterosis in B. napus (Qian et al, 2005;Li et al, 2006;Zou et al, 2010;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013;Li et al, 2014). For example, Zou et al (2010) observed a high level of heterosis in test hybrids while using germplasm diversified with the A genome of B. rapa and the C genome of B. carinata.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the value of utilizing allelic diversity of the allied Brassica species for increased heterosis in B. napus (Qian et al, 2005;Li et al, 2006;Zou et al, 2010;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013;Li et al, 2014). For example, Zou et al (2010) observed a high level of heterosis in test hybrids while using germplasm diversified with the A genome of B. rapa and the C genome of B. carinata.…”
mentioning
confidence: 99%
“…Several studies have demonstrated the value of utilizing allelic diversity of the allied Brassica species for increased heterosis in B. napus (Qian et al, 2005;Li et al, 2006;Zou et al, 2010;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013;Li et al, 2014). For example, Zou et al (2010) observed a high level of heterosis in test hybrids while using germplasm diversified with the A genome of B. rapa and the C genome of B. carinata. A number of researchers have also utilized genetic diversity of resynthesized B. napus (from B. rapa × B. oleracea interspecific cross) for the improvement of openpollinated or hybrid winter B. napus cultivars (Gehringer et al, 2007;Radoev et al, 2008;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The newly derived B. napus line may become a source of germplasm for broadening the genetic base and expanding yellow seed resources for B. napus. Importantly, by taking advantage of hybrids between the newly derived line and natural B. napus, stronger intersubgenomic heteroses between the subgenomic A j and A n , A r and A n , and C o and C n components could be studied and utilized (Zou et al 2010). From a breeding viewpoint, it is imperative that the reproductive efficiency and combining ability of the new B. napus lines, including those studied here, be properly evaluated in field trials before being used for heterosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-subgenomic heterosis may also occur in the disomic polyploid oilseed rape after partial introgression of subgenomic components from its different species (Zou et al 2010). Intensive DNA marker-aided selection in offspring ensuing from intercrossing first generation lines may assist increasing the exotic subgenomic components in further generations.…”
Section: Polyploid Heterosismentioning
confidence: 99%